Clinical and Immunological Profile of Pediatric Lupus in a Tertiary Care Hospital: A Retrospective Cross-sectional Study - Chittarvu Karishni; Bhumesh Kumar Katakam; Chintagunta Sudharani (Indian Journal of Paediatric Dermatology, 2025)
Background: Childhood-onset systemic lupus erythematosus (cSLE) is a rare, multisystem autoimmune disease with significant morbidity. It is characterized by a chronic, relapsing course and presents unique diagnostic challenges due to its diverse clinical manifestations and overlap with other pediatric conditions. Aim and objectives: This study aims to analyze the clinical and immunological profile of pediatric SLE in a tertiary care hospital. The objectives include assessing gender distribution, age at diagnosis, initial manifestations, systemic involvement, immunological markers, treatment approaches, and disease progression. Methods: A retrospective cross-sectional study was conducted in the Dermatology, Venereology, and Leprosy department at a tertiary care hospital, analyzing cases from 2007 to 2017. 20 pediatric SLE patients diagnosed based on the American College of Rheumatology (ACR) criteria were included. Data on clinical presentations, systemic involvement, laboratory findings, and treatment regimens were reviewed. Descriptive statistics and comparative analysis were performed using chi-square and t-tests, with a significance threshold of p<0.05. Results: The cohort consisted of 16 females and 4 males (4:1 ratio), with a mean age at diagnosis of 14.2 years and a mean duration from symptom onset to diagnosis of 10 months. Common initial manifestations included malar rash (80%), fever (70%), and oral ulcers (70%). Renal involvement was predominant (60%), with 40% showing grade III-IV lupus nephritis. Neuropsychiatric manifestations were observed in 25% of cases. Immunological analysis revealed ANA positivity in all patients, anti-dsDNA in 80%, and anti-Sm in 20%. Conclusion: Pediatric SLE predominantly affects females and often presents with mucocutaneous and renal involvement. Dermatologists play a crucial role in early diagnosis and management, which is essential for improving patient outcomes. Multidisciplinary collaboration is vital for comprehensive care.